STRUKTUR HUBUNGAN VOLUME PERDAGANGAN SAHAM DENGAN INFORMATION COST DAN NON-INFORMATION COST DI BURSA EFEK INDONESIA - Silalahi, Donalson (UNIKA Santo Thomas, 2012)
Most of empirical research showed that the influence of trading volume on spread did not consistent. Therefore, this study aims to explain why the influence of trading volume on spread did not consistent. In this study, the first, to estimate the decomposition of spread such as information cost and non-information cost. The second, to determine the relationship of the structure of trading volume on information cost and non-information cost. By using the data of the company's shares are traded on the Indonesia Stock Exchange during the years 2007 - 2008, in the trade size segmentation, the results showed that: information cost increases the higher the traded size so the trading volume has a positive and significant effects on the information cost. Furthermore, non-information cost did not increases the higher the traded size so the trading volume did not significantly effects on the non-information cost. Therefore, the influences of trading volume on spread depends on the decomposition of spread, such as information cost and non-information cost.